Parasioid Wasps of Eulophinae (Hymenoptera: Eulophidae) in Nusa TenggaraRA TIMUR, INDONESIA - Ubaidillah , Rosichon (Treubia, 2015)
Eulopliid parasitoid wasps of the Enlophinnc III Nusa Tenggara TIII/llr, i ndonesia, were studied taxonomicallu. A total of15 species 111 nine gellern are recorded. From those species eight are described neui to science. Keys to gel/era and species are presented.